Presentation of Discursos, volume XXVI of the Obras completas de José de la Riva Agüero Lecture delivered at the Instituto Riva-Aguero on October 25, 2017 - Pereyra Plasencia, Hugo (2018)
This dissertation presents the speeches delivered by José de la Riva Agüero y Osma (1885-1944) from his years as a student at San Marcos University until the 1930s. The analysis has identified two stages of his life, different in terms of values and worldview. From 1904 to 1919, Riva Agüero was a rationalist liberal intellectual and even anticlerical. After his European self-exile in 1919, he was influenced by the conservative intellectual atmosphere that prevailed both in Spain and Italy in the 1920s. This right-wing stage lasted after his return to Peru in 1930 until his death. Also included are reflections on his speeches as a source for reconstructing the life of Riva Agüero. It also deals with the historiographical contributions he included in them. This dissertation was read as part of the commemoration of the 73th anniversary of his death, which occurred in 1944.